Solar spectral irradiance from the CODET model for studying planetary exospheres: Earth and Mars - Rodríguez-Gómez, Jenny M. (Frontiers in Astronomy and Space Sciences, 2025)
Solar variability and solar spectral irradiance (SSI) are important for studying planetary atmospheres, particularly the ionosphere–thermosphere–mesosphere (ITM) system, and planetary exospheres. This paper introduces new SSI time series from the CODET model, obtained at different geocentric distances, namely, 3.0Re, 6.6Re, and 8.0Re (the CODET Re model), at wavelengths of 21.1nm and 19.3nm. Additionally, modeled time series at Mars’ distance (CODETMars model) are provided for 28.4nm and 21.1nm. A comparison with measurements from MAVEN/EUVM indicates that SSI modeled by the CODETMars model can be obtained with uncertainties ≤43% from 19 October 2014 to 20 April 2024. Thus, SSI from the CODET Re and CODETMars models provides an excellent opportunity to study exospheric/atmospheric dynamics and compare them with future observations. The impact of SSI on the Earth’s upper atmosphere was analyzed using the time series from the CODET model. Specifically, the study focused on the effect of SSI in extreme ultraviolet (EUV) wavelengths and its influence on the Earth’s atmosphere during geomagnetic storms, as measured by the Dst and Ap indices. This analysis shows that strong and moderate geomagnetic storms are associated with enhancements of SSI in EUV. These results highlight the importance of SSI in the study of planetary atmospheres. The CODET model provides SSI time series filling observational gaps, and providing a reliable long-term dataset that covers the last solar cycles.